Vinegars but not acetic acid are effective in reducing plasma cholesterol in hamsters fed a high-cholesterol diet. Issue 3 (20th February 2020) - Zhao, Yimin; He, Zouyan; Hao, Wangjun; Zhu, Hanyue; Liang, Ning; Liu, Jianhui; Zhang, Chengnan; Ma, Ka Ying; He, Wen-Sen; Yang, Yan; Chen, Zhen-Yu
Abstract : Vinegars reduce plasma cholesterol in hamsters given a high cholesterol diet. Abstract : The present study compares the effect of two types of vinegars, Balsamic vinegar of Modena (BV) and Chinese Shanxi vinegar (SV), with acetic acid on plasma cholesterol using hamsters as a model. Hamsters ( n = 40) were divided into five groups ( n = 8 each) with two control groups being fed a low-cholesterol diet (LCD) or a high-cholesterol diet containing 0.2% cholesterol (HCD). The three experimental groups were given a HCD diet and gavaged with 8 ml of BV, SV, and acetic acid solution (AC) per kg body weight, respectively. Acetic acid in BV, SV, and AC solutions was adjusted with water to be 20 mg ml −1 . The whole experiment lasted for 9 weeks. Plasma total cholesterol (TC) in BV and SV groups but not in the AC group was reduced by 17% and 20%, respectively, compared with that in HCD hamsters. BV and SV significantly reduced cholesterol in the liver and increased the fecal excretion of neutral sterols and bile acids. Real-time PCR analysis demonstrated that BV and SV significantly up-regulated the mRNA of cholesterol 7 alpha-hydroxylase (CYP7A1) in the liver. In conclusion, BV and SV but not AC were effective in reducing plasma TC and non-HDL-C concentrations at least in hypercholesterolemic hamsters.